High-transmittance tackifying marble glue
By formulating the high -thorium -enlargement cloud stones of components and B components, combined with the polyester and clustering reaction process, it solves the problem of difficulty in taking into account high transparency and high adhesion performance, and realizes high transparency and High -glueing intensity cloud stone gum is suitable for high -end decoration and repair occasions.
Patent Information
- Application Number
- CN202411614244.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-24
AI Technical Summary
Existing marble glue is difficult to take into account high transparency and high bonding properties, resulting in limited applications in high-end decoration fields.
By formulating high-permeability and tackifying marble glue of component A and component B, including unsaturated polyester resin liquid, toughening agent, composite anti-reflection agent and high-permeability filler, combined with the polyesterification and polycondensation reaction process, a high-permeability marble glue with high permeability is formed. Transparent and high bonding strength marble glue.
It achieves high transparency and high bonding performance of marble glue, is suitable for high-end decoration and repair occasions, and significantly improves the aesthetics and durability of stone products.
Smart Images

Figure BDA0005131734780000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of stone glue, and in particular relates to a high-transparency and tackified marble glue. Background Art
[0002] As a high-performance adhesive, marble glue plays a vital role in the field of stone processing and installation. It is mainly used for fixing and splicing stones in various paving projects.
[0003] The development of traditional marble glue mainly focuses on its bonding ability, and the requirements for transparency are not high, which to a certain extent limits its application in the field of high-end decoration. In some occasions with high requirements for aesthetics, such as high-end hotels and museums, the transparency of marble glue becomes particularly important. High-transparency marble glue can minimize the visibility of the glue layer, so that the natural texture and color of the stone can be fully presented, thereby achieving a more natural and harmonious decorative effect. High-transparency marble glue can significantly reduce the visual discontinuity at the stone joints, which will give architects who pursue the ultimate aesthetic effect more room for imagination and play.
[0004] However, the development of highly transparent marble glue faces great challenges. Existing marble glue is generally opaque or low in transparency. In order to meet the basic requirements of bonding performance, the formula generally contains a large number of non-transparent additives and fillers, which weaken the transparency of marble glue to a certain extent. At the same time, the traditional preparation process cannot effectively solve the problem of bubbles inside the colloid, resulting in a significant reduction in the transparency and aesthetics of the final product.
[0005] There are multiple challenges in developing highly transparent marble glue. Currently, most of the marble glues on the market are opaque or have low transparency. In order to achieve the necessary bonding strength, their formulas often contain a large number of non-transparent additives and fillers, which directly affect the transparency of the marble glue. At the same time, there are often tiny bubbles inside the marble glue, which further reduces the transparency and appearance quality of the product. Therefore, how to improve the transparency of marble glue while ensuring good bonding performance is not only a technical problem, but also has important practical application value. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a high-transparency and tackified marble glue, aiming to solve the problem that the marble glue in the prior art is difficult to achieve both high transparency and high bonding performance, and to provide a marble glue that not only has excellent bonding strength but also maintains extremely high transparency, and is suitable for various decorative and repair occasions with high requirements for aesthetics.
[0007] The high-transparency and tackifying marble glue provided by the present invention comprises a component A and a component B which are mixed evenly:
[0008] Among them, component A includes:
[0009] Unsaturated polyester resin liquid 1000-1200 parts by mass;
[0010] Toughener 25-55 parts by mass;
[0011] 15-30 parts by weight of composite permeability enhancer;
[0012] The first part is 300-650 parts by weight of high permeability filler;
[0013] Wherein, component B includes components:
[0014] Peroxide initiator 850-1250 parts by mass;
[0015] The second part is 350-750 parts by weight of high-transparency filler.
[0016] As a further optimization scheme of the above-mentioned high-transparency and tackified marble glue, in component A, the toughening agent is chlorinated paraffin or maleic acid polyisobutylene.
[0017] As a further optimization scheme for the above-mentioned high-transmittance and thickening marble glue, in component A, the composite permeability enhancer includes: dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR additive.
[0018] As a further optimization scheme for the above-mentioned high-transmittance and thickening marble glue, in component A, the composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR additive in a mass ratio of 100:(55-85):(5-10):(15-40):(15-30).
[0019] As a further optimization solution for the above-mentioned high-transparency and tackified marble glue, the CERAFLOUR additive is selected from at least one of CERAFLOUR1003 and CERAFLOUR 1004.
[0020] As a further optimization scheme of the above-mentioned high-transparency and tackified marble glue, in component B, the peroxide initiator is benzoyl peroxide.
[0021] As a further optimization scheme for the above-mentioned high-transparency thickening marble glue, in component A and component B, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness between 80-94 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0022] As a further optimization scheme for the above-mentioned high-transparency and thickening marble glue, the preparation of unsaturated polyester resin liquid includes the following steps: 1000 parts by mass of polyol, 600-800 parts by mass of maleic acid, 150-350 parts by mass of fumaric acid, 500-750 parts by mass of phthalic anhydride, 350-450 parts by mass of adipic anhydride, and 600-900 parts by mass of styrene; carrying out polyesterification condensation reaction at a reaction temperature of 195-215° C. for 3-5 hours under stirring, and finally adding 500-850 parts by mass of styrene to obtain the unsaturated polyester resin liquid.
[0023] As a further optimization scheme for the above-mentioned high-transparency thickening marble glue, in the process of preparing the unsaturated polyester resin liquid, first add 1000 parts by mass of polyol into the reaction container; then add 600-800 parts by mass of maleic acid, 150-350 parts by mass of fumaric acid, 500-750 parts by mass of phthalic anhydride and 350-450 parts by mass of adipic anhydride into the reaction container; then add 600-900 parts by mass of styrene; turn on the heating device of the reaction container, wait for the temperature inside the reaction container to rise to 80°C and then start the stirring device, wait for the temperature inside the reaction container to rise to 195-215°C and then maintain the temperature constant for reaction.
[0024] As a further optimization scheme for the above-mentioned high-transmittance thickening marble glue, during the polyesterification polycondensation reaction, the water generated by the reaction in the system is discharged through a condenser on the reaction container.
[0025] Beneficial Effects
[0026] The high-transparency and tackified marble glue provided by the present invention has excellent bonding strength, can effectively bond various materials such as stone materials, and meets the requirement for high bonding strength of marble glue in practical applications.
[0027] The high-transparency and tackified marble glue provided by the present invention also has excellent transparency. The marble glues in all embodiments show a low haze value. The prepared marble glue has high transparency and is almost invisible visually, and is suitable for applications that particularly emphasize aesthetic decoration.
[0028] The high-transparency and high-strength marble glue provided by the present invention is particularly suitable for the repair and decoration of stone materials, and can effectively improve the aesthetics and durability of stone products. In addition to the field of stone materials, the marble glue is also expected to be expanded to the bonding of materials such as glass and ceramics to meet the needs of high transparency and high strength bonding. DETAILED DESCRIPTION
[0029] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0030] Preparation of unsaturated polyester resin liquid: at normal temperature and pressure, first add 1000 parts by mass of propylene glycol to a reactor, then add 600-800 parts by mass of maleic acid, 150-350 parts by mass of fumaric acid, 500-750 parts by mass of phthalic anhydride and 350-450 parts by mass of adipic anhydride, and then add 600-900 parts by mass of styrene. Turn on the heating system of the reactor and gradually increase the temperature in the reactor. When the temperature rises to 80°C, start the agitator and stir mechanically to fully mix the raw materials. The reactor continues to heat up to the reaction temperature, and the reaction temperature is controlled between 195-215°C, and the polyesterification polycondensation reaction is carried out for 3-5 hours. During the reaction, water is discharged through a condenser. Then, 500-850 parts by mass of styrene are added while hot to obtain an unsaturated polyester resin liquid.
[0031] According to the following formula, component A and component B are mixed evenly to prepare components A and B of high-transmittance and tackifying marble glue.
[0032] Among them, component A includes the following components:
[0033] Unsaturated polyester resin liquid 1000-1200 parts by mass;
[0034] Toughener 25-55 parts by mass;
[0035] 15-30 parts by weight of composite permeability enhancer;
[0036] The first part is 300-650 parts by weight of high-transparency filler.
[0037] Among them, component B includes the following components:
[0038] Peroxide initiator 850-1250 parts by mass;
[0039] The second part is 350-750 parts by weight of high-transparency filler.
[0040] In component A, the toughening agent is chlorinated paraffin or maleic acid polyisobutylene.
[0041] In component A, the composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR additive in a mass ratio of 100:(55-85):(5-10):(15-40):(15-30), wherein the CERAFLOUR additive is selected from at least one of CERAFLOUR 1003 and CERAFLOUR 1004.
[0042] In component B, the peroxide initiator is: benzoyl peroxide.
[0043] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness of 88 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0044] Example 1
[0045] At normal temperature and pressure, add 1000 parts by mass of propylene glycol to the reactor, followed by 600 parts by mass of maleic acid, 150 parts by mass of fumaric acid, 500 parts by mass of phthalic anhydride and 350 parts by mass of adipic anhydride, and then add 600 parts by mass of styrene. Start the heating system, and when the temperature rises to 80°C, start the agitator and mechanically stir to fully mix the raw materials. Continue heating until the reaction temperature rises to 195°C, and carry out a polyesterification polycondensation reaction at this temperature for 3 hours. During the reaction, water is discharged through a condenser. After the reaction is completed, add 600 parts by mass of styrene while hot to obtain an unsaturated polyester resin liquid.
[0046] Component A: 1200 parts by mass of unsaturated polyester resin liquid, 55 parts by mass of toughening agent, 30 parts by mass of composite permeability enhancer, and 650 parts by mass of the first part of high permeability filler. The toughening agent is chlorinated paraffin. The composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR104 additive in a mass ratio of 100:55:5:15:15.
[0047] Component B: 1250 parts by weight of peroxide initiator and 750 parts by weight of the second part of high-transparency filler. The peroxide initiator is benzoyl peroxide.
[0048] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness between 80 degrees, a particle size distribution within 1250 meshes to 5000 meshes, and a water content less than 0.1%.
[0049] Example 2
[0050] At normal temperature and pressure, add 1000 parts by mass of propylene glycol to the reactor, followed by 800 parts by mass of maleic acid, 350 parts by mass of fumaric acid, 750 parts by mass of phthalic anhydride and 450 parts by mass of adipic anhydride, and then add 900 parts by mass of styrene. Start the heating system, and when the temperature rises to 80°C, start the agitator and mechanically stir to fully mix the raw materials. Continue heating until the reaction temperature rises to 210°C, and carry out a polyesterification polycondensation reaction at this temperature for 5 hours. During the reaction, water is discharged through a condenser. After the reaction is completed, 900 parts by mass of styrene are added while hot to obtain an unsaturated polyester resin liquid.
[0051] Component A: 1100 parts by mass of unsaturated polyester resin liquid, 40 parts by mass of toughening agent, 20 parts by mass of composite permeability enhancer, and 500 parts by mass of the first part of high permeability filler. The toughening agent is chlorinated paraffin. The composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR104 additive in a mass ratio of 100:85:10:40:30.
[0052] - Component B: 1000 parts by weight of peroxide initiator and 500 parts by weight of the second part of high-transmittance filler. The peroxide initiator is benzoyl peroxide.
[0053] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness of 88 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0054] Example 3
[0055] At normal temperature and pressure, add 1000 parts by mass of propylene glycol to the reactor, followed by 700 parts by mass of maleic acid, 250 parts by mass of fumaric acid, 625 parts by mass of phthalic anhydride and 400 parts by mass of adipic anhydride, and then add 750 parts by mass of styrene. Start the heating system, and when the temperature rises to 80°C, start the agitator and mechanically stir to fully mix the raw materials. Continue heating until the reaction temperature rises to 208°C, and carry out a polyesterification polycondensation reaction at this temperature for 4 hours. During the reaction, water is discharged through a condenser. After the reaction is completed, 750 parts by mass of styrene are added while hot to obtain an unsaturated polyester resin liquid.
[0056] Component A: 1000 parts by mass of unsaturated polyester resin liquid, 25 parts by mass of toughening agent, 15 parts by mass of composite permeability enhancer, and 300 parts by mass of the first part of high permeability filler. The toughening agent is chlorinated paraffin. The composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR103 additive in a mass ratio of 100:65:8:30:22.
[0057] Component B: 850 parts by weight of peroxide initiator and 350 parts by weight of the second part of high-transmittance filler. The peroxide initiator is benzoyl peroxide.
[0058] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness of 88 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0059] Example 4
[0060] At normal temperature and pressure, add 1000 parts by mass of propylene glycol to the reactor, followed by 650 parts by mass of maleic acid, 200 parts by mass of fumaric acid, 600 parts by mass of phthalic anhydride and 375 parts by mass of adipic anhydride, and then add 700 parts by mass of styrene. Start the heating system, and when the temperature rises to 80°C, start the agitator and mechanically stir to fully mix the raw materials. Continue heating until the reaction temperature rises to 205°C, and carry out a polyesterification polycondensation reaction at this temperature for 3.5 hours. During the reaction, water is discharged through a condenser. After the reaction is completed, 700 parts by mass of styrene are added while hot to obtain an unsaturated polyester resin liquid.
[0061] Component A: 1050 parts by mass of unsaturated polyester resin liquid, 45 parts by mass of toughening agent, 25 parts by mass of composite permeability enhancer, and 450 parts by mass of the first part of high permeability filler. The toughening agent is maleic acid polyisobutylene. The composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR103 additive in a mass ratio of 100:65:8:30:22.
[0062] Component B: 1050 parts by weight of peroxide initiator and 500 parts by weight of the second part of high-transmittance filler. The peroxide initiator is benzoyl peroxide.
[0063] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness of 88 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0064] Example 5
[0065] At normal temperature and pressure, add 1000 parts by mass of propylene glycol to the reactor, followed by 750 parts by mass of maleic acid, 300 parts by mass of fumaric acid, 675 parts by mass of phthalic anhydride and 425 parts by mass of adipic anhydride, and then add 800 parts by mass of styrene. Start the heating system, and when the temperature rises to 80°C, start the agitator and mechanically stir to fully mix the raw materials. Continue heating until the reaction temperature rises to 200°C, and carry out a polyesterification polycondensation reaction at this temperature for 4.5 hours. During the reaction, water is discharged through a condenser. After the reaction is completed, 800 parts by mass of styrene are added while hot to obtain an unsaturated polyester resin liquid.
[0066] Component A: 1150 parts by mass of unsaturated polyester resin liquid, 30 parts by mass of toughening agent, 20 parts by mass of composite permeability enhancer, and 400 parts by mass of the first part of high permeability filler. The toughening agent is maleic acid polyisobutylene. The composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR104 additive in a mass ratio of 100:65:8:30:22.
[0067] Component B: 950 parts by weight of peroxide initiator and 600 parts by weight of the second part of high-transparency filler. The peroxide initiator is benzoyl peroxide.
[0068] In the A and B components, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness of 88 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
[0069] The marble glues prepared in the above embodiments and comparative examples were tested for bonding performance and transparency.
[0070] The bonding performance test of marble glue refers to the standard "JC / T 989-2016 Non-structural Load-bearing Stone Adhesive". Steel plate specimens with specifications of 100mm×25mm×2mm are selected, and the bonding surface is cleaned and dried; then, the A component and the B component of the marble glue are mixed in proportion, and after being fully stirred, they are evenly applied on the bonding surface of a steel plate, and another steel plate is attached to it, and slight pressure is applied to ensure that the two steel plates are in close contact; next, the bonded specimens are placed in standard environmental conditions (temperature 23±2℃, relative humidity 50±5%) for curing for 24 hours; after curing, the specimens are installed on the universal testing machine, the loading speed is set to (5±1)mm / min, and the testing machine is started to record the maximum load value when the specimen is destroyed; finally, the compressive shear bond strength is calculated according to the maximum load value and the bonding area, and the unit is MPa. Five specimens of each sample are tested, and the average value is taken as the final result and recorded in Table 1.
[0071] The transparency test of marble glue refers to the standard "GB / T 2410-2008 Determination of light transmittance and haze of transparent plastics". Mix component A and component B in proportion, stir well and avoid bubbles. Pour the mixed colloid into a pre-prepared mold with a size of 100mm×100mm×4mm, and ensure that the surface is flat. Curing for 24 hours under standard environmental conditions (temperature 23±2℃, relative humidity 50±5%) to ensure that the colloid is completely cured. Use a pre-calibrated haze meter to test the sample, select the "haze" mode, aim the light source at the sample, and record the haze value. Repeat the measurement 5 times, take the average value as the final haze result and record it in Table 1.
[0072] Table 1 Performance test results
[0073]
[0074] It can be seen from the experimental results of the above five embodiments that the prepared high-transmittance and tackified marble glue exhibits very excellent comprehensive performance.
[0075] In terms of bonding performance, the marble glues of all examples showed high compressive shear bonding strength and bonding bending strength, indicating that the prepared marble glue has excellent bonding strength and can effectively bond materials such as stone, meeting the high strength requirements in practical applications. This excellent bonding performance is mainly attributed to the good compatibility between the unsaturated polyester resin liquid and the toughening agent, and the stable three-dimensional network structure formed during the polyesterification polycondensation reaction, which enhances the overall mechanical properties of the material.
[0076] In terms of transparency, the marble glue of all embodiments has a low haze value, the lowest of which can reach 0.9%, indicating that it has high transparency, which is mainly attributed to the combined effect of the composite permeability enhancer and the high-transparency filler. The composite permeability enhancer, dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, CERAFLOUR additive and other ingredients work together with the unsaturated resin body to effectively improve the transparency and glossiness of the marble glue by reducing the system tension, promoting the elimination of microbubbles in the system, and improving the system uniformity and interface characteristics. The high-purity, fine-grained acid-washed silica powder as a filler not only enhances the mechanical properties of the material, but also maintains a high transparency, making the marble glue almost invisible visually, and suitable for applications requiring beautiful decoration.
[0077] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-transparency and tackifying marble glue, characterized by: It includes component A and component B which are mixed evenly. Among them, component A includes: Unsaturated polyester resin liquid 1000-1200 parts by mass; Toughener 25-55 parts by mass; 15-30 parts by weight of composite permeability enhancer; The first part is 300-650 parts by weight of high permeability filler; Wherein, component B includes components: Peroxide initiator 850-1250 parts by mass; The second part is 350-750 parts by weight of high-transparency filler.
2. The high-transmittance and tackifying marble glue according to claim 1, characterized in that: In component A, the toughening agent is chlorinated paraffin or maleic acid polyisobutylene.
3. The high-transmittance and tackifying marble glue according to claim 1, characterized in that: In component A, the composite permeability enhancer includes: dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR additive.
4. The high-transmittance and tackifying marble glue according to claim 3, characterized in that: In component A, the composite permeability enhancer is a mixture of dibutyl phthalate, hydrogenated castor oil, di-n-butyltin dilaurate, polyvinyl pyrrolidone, and CERAFLOUR additive in a mass ratio of 100:(55-85):(5-10):(15-40):(15-30).
5. The high-transmittance and tackifying marble glue according to claim 4, characterized in that: The CERAFLOUR adjuvant is selected from at least one of CERAFLOUR 1003 and CERAFLOUR 1004.
6. The high-transmittance and tackifying marble glue according to claim 1, characterized in that: In component B, the peroxide initiator is benzoyl peroxide.
7. The high-transmittance and tackifying marble glue according to claim 1, characterized in that: In component A and component B, the high-transparency filler is acid-washed silica powder with a purity greater than 99.5%, a whiteness between 80 and 94 degrees, a particle size distribution within 1250 mesh to 5000 mesh, and a water content less than 0.1%.
8. The high-permeability and tackifying marble glue according to any one of claims 1 to 7, characterized in that: Preparation of unsaturated polyester resin solution The method comprises the following steps: 1000 parts by mass of polyol, 600-800 parts by mass of maleic acid, 150-350 parts by mass of fumaric acid, 500-750 parts by mass of phthalic anhydride, 350-450 parts by mass of adipic anhydride and 600-900 parts by mass of styrene are mixed; the mixture is subjected to polyesterification polycondensation reaction at a reaction temperature of 195-215° C. for 3-5 hours under stirring, and finally 500-850 parts by mass of styrene is added to obtain the unsaturated polyester resin liquid.
9. The high-transmittance and tackifying marble glue according to claim 8, characterized in that: In the process of preparing unsaturated polyester resin liquid, 1000 parts by mass of polyol is first added into a reaction container; then 600-800 parts by mass of maleic acid, 150-350 parts by mass of fumaric acid, 500-750 parts by mass of phthalic anhydride and 350-450 parts by mass of adipic anhydride are added into the reaction container; then 600-900 parts by mass of styrene are added; the heating device of the reaction container is turned on, and the stirring device is started after the temperature inside the reaction container rises to 80° C., and after the temperature inside the reaction container rises to 195-215° C., the temperature is maintained constant for reaction.
10. The high-transparency and tackifying marble glue according to claim 9, characterized in that: During the polyesterification polycondensation reaction, the water generated by the reaction in the system is discharged through the condenser on the reaction container.